OPTIMIZATION OF GYM CHECK IN AND MEMBERSHIP INFORMATION SYSTEM QR CODE SCANNER BASED - Badriah, Nurul; Veri Shandy, Sony (Universitas Utpadaka Swastika, 2024)
The development of information technology provides opportunities to improve operational efficiency in various fields, including membership management at gyms. A QR code scanner-based information system is an effective solution for managing gym member check in. Users can check in simply by scanning a QR code that is linked to their membership data. This system not only facilitates the attendance process but also helps managers monitor the number of member check in, remaining attendance quota, and attendance time. This researcaims to design and implement a QR code scanner-based check in system at the gym, as well as analyze the impact of the system on operational efficiency.